O gaúcho e o colono : variações de um discurso mítico nas eleições municipais de 1996 e 2000 em Caxias do Sul - Gonçalves, Silvana Teresinha Tomazzoni (My University, 2016)
This paper analyzes the construction of political discourse related to the gaúcho (typical cowboy who lives in the southern state of Brazil, Rio Grande do Sul) and the colono (settler) in the 1996 and 2000 municipal elections, in Caxias do Sul. The research was delimited by the electoral programs of the Popular Front and it seeks to demonstrate how the myths of these two social groups are present in the social imaginary and end up being used in partisan communication with the purpose of winning voters. Twenty Popular Front campaign programs were analysed. These referred to the 1996 elections for the City Hall of Caxias do Sul between the State Deputy, Pepe Vargas, from PT, and the Federal deputy, Germano Rigoto, from PMDB. In the year of 2000, José ivo Sartori was the one running against Pepe Vargas. In order to move forward in this direction, we have identified the gaúcho and Italian immigrant process of identity formation and subsequently the way this identity will become the collective imagination in a persuasive process of historical, literary and media discourse. Through anthropological and semiotic analysis, whose theoretical framework is based on Mircea Eliade and Roland Barthes, we found the meanings produced by these messages to interpret the variations of a mythologized election discourse, which seeks a rapprochement with the voter based on his/her identification with the myth.
Este trabalho analisa a construção dos discursos políticos relacionados ao gaúcho e ao colono nas eleições municipais de 1996 e 2000, em Caxias do Sul. Delimitada pelos programas eleitorais da Frente Popular, a pesquisa busca demonstrar como os mitos desses dois grupos sociais estão presentes no imaginário social e acabam sendo empregados na comunicação partidária com o propósito de conquistar os eleitores. Foram analisados 20 programas da campanha da Frente Popular que, em 1996, disputou a Prefeitura de Caxias do Sul com o então deputado estadual Pepe Vargas, do PT, tendo como adversário o deputado federal Germano Rigotto, do PMDB, e, no ano de 2000, concorreu com o também deputado federal José Ivo Sartori. Para avançar nesse sentido, identificamos o processo de formação da identidade do gaúcho e do imigrante italiano e, posteriormente, a forma com que essa identidade passa a constituir o imaginário coletivo em um processo persuasivo de discurso histórico, literário e midiático. Por meio de análises antropológicas e semióticas, cujo aporte teórico baseia-se em Mircea Eliade e Roland Barthes, verificamos os significados produzidos por essas mensagens para interpretar as variações de um discurso eleitoral mitificado, que busca uma aproximação com o eleitor a partir de sua identificação com o mito.
Keywords: Análise crítica do discurso; Mito; Ciência política; Comunicação de massa e cultura; Eleições municipais; Critical discourse analysis; Myth; Political science; Mass media and culture; Election